Odours and Boundaries: Bora-Miraña Construction of Territoriality (Amazonia) - Karadimas, Dimitri (Ethnologies, 2013)
The concept of territoriality is often linked to a more global apprehension of land seen as being limited by borders with neighboring groups. Within the Bora-Miraña Amerindian group of Colombian Amazon, it seems that this concept of territoriality is not so much linked to delimitation of factual and located boundaries as it is with a more vague notion of territorial odour or smell. The notion relies on the perception of individual healthiness and on diseases seen as been widespread by other groups or by animals seen as enemies. The virulence of “others” can thus only be contained thanks to a stronger local odour that characterizes the self.